Factors associated with overweight and obesity in Mexican school-age children: results from the National Nutrition Survey 1999 Factores asociados con sobrepeso y obesidad en niños mexicanos de edad escolar: resultados de la Encuesta Nacional de Nutrición, 1999 - Bernardo Hernández; Lucía Cuevas-Nasu; Teresa Shamah-Levy; Eric A Monterrubio; Claudia Ivonne Ramírez-Silva; Raquel García-Feregrino; Juan A Rivera; Jaime Sepúlveda-Amor (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: The objective of the study was to measure the prevalence of overweight and obesity in Mexican school-age children (5-11 years) in the National Nutrition Survey 1999 (NNS-1999). MATERIAL AND METHODS: Overweight and obesity (defined as an excess of adipose tissue in the body) were evaluated through the Body Mass Index (BMI) in 10,901 children, using the standard proposed by the International Obesity Task Force. Sociodemographic variables were obtained using a questionnaire administered to the children's mothers. RESULTS: The national prevalence of overweight and obesity was reported to be 19.5%. The highest prevalence figures were found in Mexico City (26.6%) and the North region (25.6%). When adjusting by region, rural or urban area, sex, maternal schooling, socioeconomic status, indigenous ethnicity and age, the highest prevalences of overweight and obesity were found among girls. The risks of overweight and obesity were positively associated with maternal schooling, children's age and socioeconomic status. CONCLUSIONS: Overweight and obesity are prevalent health problems in Mexican school-age children, particularly among girls, and positively associated with socioeconomic status, age, and maternal schooling. This is a major public health problem requiring preventive interventions to avoid future health consequences. OBJETIVO: Documentar las prevalencias de sobrepeso y obesidad en niños mexicanos en edad escolar (5 a 11 años de edad) obtenidas de la Encuesta Nacional de Nutrición en 1999 (ENN-1999). MATERIAL Y MÉTODOS: El sobrepeso y la obesidad (definida como un exceso de tejido adiposo en el organismo) se evaluaron a través del Indice de Masa Corporal (IMC) en 10 901 niños, tomando como patrón de referencia el propuesto por el International Obesity Task Force. Las variables sociodemográficas se obtuvieron a partir de un cuestionario aplicado a la madre del niño. RESULTADOS: La prevalencia nacional de sobrepeso y obesidad fue de 19.5%. Las prevalencias más altas se encontraron en la Ciudad de México (26.6%) y en la región norte (25.6%). Al ajustar por región, zona rural o urbana, sexo, escolaridad de la madre, nivel socioeconómico, edad e indigenismo, los mayores riesgos de sobrepeso y obesidad se encontraron en niñas; el riesgo de obesidad y sobrepeso se asoció positivamente con la escolaridad de la madre, con el nivel socioeconómico y con la edad de los escolares. CONCLUSIONES: El sobrepeso y obesidad son problemas de salud de alta prevalencia en niños en edad escolar en México, especialmente en niñas, y se asocia positivamente con el nivel socioeconómico, la edad de los escolares y la escolaridad de las madres. Este es un problema de salud pública que requiere acciones de prevención para evitar riesgos en la salud en un futuro.